Digital competencies and development strategies of librarians at Universitas Negeri Padang in 4.0 era - Nabila, Jeihan; Pangesti, Nesa Riska; Utami, Riski Gusri (Universitas Padjadjaran, 2025)
Rapid digital transformation in the Industrial Revolution 4.0 era has shifted academic libraries into digital resource hubs, requiring librarians to adapt their competencies to meet the ever-evolving demands. This study is urgently needed to explore how the digital competency gap among librarians affects the effectiveness of library services in the digital era. This study aimed to measure the transformation of Universitas Negeri Padang Librarians in Industry 4.0. The research method used a sequential explanatory mixed-methods design, combining a cross-sectional survey of all 26 UNP librarians with follow-up in-depth interviews. The competencies assessed included device and software operation, information and data literacy, communication and collaboration, digital content creation, security, problem-solving, and self-development. Results showed that librarians excelled in basic skills such as ensuring internet connectivity (M = 7.08, SD = 1.055) and maintaining ethical digital communication (M = 6.85, SD = 1.190). However, challenges persisted in advanced areas such as software troubleshooting (M = 5.96, SD = 1.509) and creating innovative digital solutions to improve patron experience (M = 4.85, SD = 1.736). Interviews revealed a high dependency on technical support, limiting librarians’ independence in solving technical problems. The findings underscored the need for targeted training in problem-solving, digital innovation, and advanced application use, supported by improved infrastructure and access to sophisticated tools. This study concludes that improving the digital competencies of librarians is essential to support sustainable digital library services and strengthen the development of library science in Indonesia.